An experimental and numerical study of reinforced ultra-high performance concrete slabs under blast loads - Li, J.; Wu, C.; Hao, Hong (Elsevier Ltd, 2015)
Ultra-high performance concrete (UHPC) which is characterized by high strength, high ductility and high toughness has been widely applied in modern structure construction. Outstanding mechanical feature of UHPC not only enables strong yet slim structure design but also highlights its potential in protective engineering against extreme loads like impact or explosion. In this research a series of reinforced concrete slabs are tested to determine their response under explosive loading conditions. Concrete materials used in the slab construction are ultra-high strength concrete (UHPC) and normal strength concrete (NSC). In total five slabs are tested including four UHPC slabs with varying reinforcement ratios and one control NSC slab with normal reinforcement. Explosive charges with TNT equivalent weights ranging from 1.0 to 14.0 kg at scaled distances ranging from 0.41 to 3.05m/kg1/3 are used in the current experiments. Test results verified the effectiveness of UHPC slabs against blast loads. Numerical models are established in LS-DYNA to reproduce the field blast tests on UHPC slabs. The numerical results are compared with the field test data, and the feasibility and validity of the numerical predictions of UHPC slab responses are demonstrated.